2017
DOI: 10.1016/j.shaw.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxic Chemicals at Work and Efforts to Protect Workers' Health: A Literature Review

Abstract: A huge number of chemicals are produced and used in the world, and some of them can have negative effects on the reproductive health of workers. To date, most chemicals and work environments have not been studied for their potential to have damaging effects on the workers' reproductive system. Because of the lack of information, many workers may not be aware that such problems can be related to occupational exposures. Newly industrialized countries such as Republic of Korea have rapidly amassed chemicals and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…Men exposed to hazardous substances in their workplace, including solvents, insecticides, adhesives, silicones and radiation, exposure to these and similar substances can lead to infertility. 82,112,113 Exposure to radiation can lead to reduced sperm production, and exposure to high doses can lead to complete infertility. Overuse of the sun bath can also lead to a temporary decrease in sperm count.…”
Section: Environment and Lifestylementioning
confidence: 99%
“…Men exposed to hazardous substances in their workplace, including solvents, insecticides, adhesives, silicones and radiation, exposure to these and similar substances can lead to infertility. 82,112,113 Exposure to radiation can lead to reduced sperm production, and exposure to high doses can lead to complete infertility. Overuse of the sun bath can also lead to a temporary decrease in sperm count.…”
Section: Environment and Lifestylementioning
confidence: 99%
“…The reproductive system is considered to be the most vulnerable system toward a huge number of chemicals and drugs (Rim, 2017). Several studies have been demonstrated that SSRIs use inhibits nitric oxide synthase (NOS) activity and reproductive hormonal pro ile synthesis, which plays a major role in stimulating libido, penile erection and orgasm phase and consequently could contribute to male factor infertility (Brezina et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are well established data regarding chemicals hazardous to reproductive health, but there are still unknown latent hazards; especially for commercial chemical products that are considered as trade secrets. Moreover, there are fewer human epidemiological data than animal experimental data, which makes it more difficult to interpret their real-world health effects [3]. For these reasons, it is hard to assess how many risks are there in workplaces, how many workers are exposed to hazards, and which agents are concerned.…”
Section: Introductionmentioning
confidence: 99%